517 Glioblastoma Induces the Recruitment of Anti-Tumoral Immunostimulatory Neutrophils from Skull Bone Marrow. (April 2023) - Lad, Meeki; Beniwal, Angad; Gill, Sabraj; Jain, Saket; Aghi, Manish Kumar
Abstract : INTRODUCTION: The effects of tumor-associated neutrophils (TANs) on glioblastoma biology remain poorly understood. While TANs are generally considered immunosuppressive, recent studies have demonstrated their ability to present antigen to T cells, warranting investigation of this phenotype in glioblastoma. METHODS: Flow cytometry was used to sort and characterize surface protein expression among neutrophils across 5 newly diagnosed glioblastoma fresh tissue specimens. Samples were evaluated transcriptomically via single-cell RNA sequencing (scRNA-seq) or phenotypically via coculture with autologous T cells. TANs were further evaluated in a syngeneic glioma mouse model (Balb/c), treated with either neutrophil-depleting antibody (αLy6G) or isotype control; tumor size was ascertained by bioluminescent imaging. Skull bone marrow was tagged with fluorescent dye in neutrophil tracing experiments. RESULTS: 21.0-34.1% of patient glioblastoma TANs express MHCII, a marker of antigen-presenting cells not canonically associated with neutrophils and not expressed in matched peripheral blood (PBNs). scRNA-seq pseudotime analysis demonstrates that antigen-presenting neutrophils are a developmental lineage seen uniquely in TANs and not PBNs, with enriched expression of MHCII subunits (HLA-DR), chaperones (HLA-DM), and costimulatory ligands (CD86/83;). Consequently, TANs activate T cells in an MHCII-dependent manner (CD25 MFI fold-change, PBNs vs TANs: 1.1 vs 3.2, p < 0.001), and depleting neutrophils in a murine model yields endpoint tumors that have 53% lower CD8+ T cell infiltration (n = 13, p = 0.0024) and are 2.4-fold larger (p = 0.0383). The lack of MHCII+ neutrophils in blood suggests that these cells may be recruited from local marrow niches and not circulation; indeed, in vivo, we observe that compared to all TANs, MHCII+ TANs are disproportionately derived from skull bone marrow (41.7% vs 9.3%). CONCLUSIONS: Given the recruitment of immunostimulatory TANs from the calvarium to the glioblastoma microenvironment, mechanisms to enhance neutrophil transmarrow migration may have therapeutic value.